(untitled) - İlknur Yeşilçinar; Eda Şahin; Gülten Güvenç (Central European Journal of Nursing and Midwifery, 2022)
Aim: To identify the validity and reliability of the Turkish version of the Pregnancy Experience Scale-Brief Version (PES-Brief). Design: A methodological study. Methods: The sample of this methodological research consisted of 201 pregnant women. Face, language, content, construct, and convergent validity analyses were used. The retest was administered to 40 randomly selected pregnant women in the sample after four weeks from the first data collection. Results: The Cronbach alpha score of PES-Brief for uplifts was 0.77 and 0.87 for the retest. The Turkish version was found to be grouped under two factors. Conclusion: Turkish translated version of PES-Brief is a valid and reliable instrument to assess pregnant women's positive or negative perceptions. The PES-Brief may be a time-saving tool to assess negative and positive pregnancy experiences.